Essays on international capital flows to developing countries - Keskinsoy, Bilal (2012)
This thesis investigates international capital flows to developing countries for the period 1970-2006. The first chapter introduces the theoretical and empirical framework of the thesis, motivates it, overviews its building blocks (i.e. the following chapters) and clarifies its approach to the balance of payments. The second chapter reviews the data and shows the overall trends and developments in capital flows to the developing world by focusing on the geographical regions and income groups.